Telephone fraud or the problem of modern Kyrgyzstan (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2024)
In the article, the author considers one of the problems of modern Kyrgyzstan in the field of combating the facts of telephone fraud, as well as problems and there will be a solution. The study of this topic is of very wide interest both from the scientific intelligentsia and from the law enforcement agencies of the Kyrgyz Republic. All this is due to the fact that the development of information technology is reaching the advanced level, requiring more and more attention and control. The article also talked about the need to amend the legislation of the Kyrgyz Republic regulating relations in the field of electric and postal communications.
Keywords: Crime, telephone fraud, sim-cards, electric and postal communication, cellular communication, mobile operator, mobile application, cellular device, cybercrime, legislation, subscriber, penitentiary institutions, convicts, telephone option, subscriber registration, information technology, online stores, online services, online payment, mobile wallet, special contingent